Comet assay in evaluating deoxyribonucleic acid damage after out-of-hospital cardiac arrest - Hazuková, Radka; Rezácová, Martina; Köhlerová, Renata; Tomek, Tomáš; Cermáková, Eva; Kocí, Jaromír; Pleskot, Miloslav (Anadolu kardiyoloji dergisi, 2017)
OBJECTIVE: This study aimed to investigate whether out-of-hospital cardiac arrest (OHCA) may induce severe DNA damage measured using comet assay in successfully resuscitated humans and to evaluate a short-term prognostic role. METHODS: In this prospective, controlled, blinded study (1/2013-1/2014), 41 patients (age, 63±14 years) successfully resuscitated from non traumatic OHCA and 10 healthy controls (age, 53±17 years) were enrolled. DNA damage [double-strand breaks (DSBs) and single-strand breaks (SSBs)] was measured using comet assay in peripheral lymphocytes sampled at admission. Clinical data were recorded (according to Utstein style). A good short-term prognosis was defined as survival for 30 days. RESULTS: Among the patients, there were 71% (29/41) short-term survivors. After OHCA, DNA damage (DSBs and SSBs) was higher (11.0±7.6% and 0.79±2.41% in tail) among patients than among controls (1.96±1.63% and 0.02±0.03% in tail), and it was more apparent for DSBs (p<0.001 and p=0.085). There was no difference in the DNA damage between patients with cardiac and non-cardiac etiology, or between survivors and nonsurvivors. Among Utstein style parameters, ventricular fibrillation, asystole, and early electrical defibrillation influenced DSBs; none of the factors influenced SSBs. Factors influencing survival were SSBs, ventricular fibrillation, length of cardiopulmonary resuscitation by professionals ≤15 min, cardiogenic shock, and postanoxic encephalopathy. In contrast to DSBs [area under the curve (AUC)=0.520], SSBs seem to have a potential in prognostication (AUC=0.639). CONCLUSION: This study for the first time demonstrates revelation of DNA damage using comet assay in patients successfully resuscitated from OHCA. Whether DNA damage measured using comet assay may be a prognostic marker remains unknown, although our data may encourage some suggestions.
Keywords: dospělí; DNA Damage; Female; kardiopulmonální resuscitace; lymfocyty; Adult; ženské pohlaví; elektrická defibrilace; Cardiopulmonary Resuscitation; Out-of-Hospital Cardiac Arrest; lidé; dvojitá slepá metoda; Survival Analysis; Sensitivity and Specificity; Electric Countershock; studie případů a kontrol; Aged, 80 and over; senzitivita a specificita; Turkey; zástava srdce mimo nemocnici; prognóza; Turecko; poškození DNA; prospektivní studie; Double-Blind Method; Male; Case-Control Studies; Aged; Comet Assay; Prospective Studies; Prognosis; analýza přežití; Lymphocytes; kometový test; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans